PENGARUH KOMUNIKASI INTERNAL TERHADAP KINERJA PELAYANAN FUNGSIONARIS GEREJA KRISTEN JAWA KLAMPOK - Andreas Tri Febriantoro; Heru Kristanto (Management and Sustainable Development Journal, 2024)
One of the determining factors for the success of an organization is the performance and productivity of employees. One way is to improve employee performance with good inter-line communication. Good internal communication can improve performance so as to achieve the expected goals. The purpose of this research is to find outthe effect of internal communication on the performance of functional service of the Javanese Klampok Christian Church, Banjarnegara Regency. The research results obtained were mostly male, 32 (52.5%), in the age category 36-45 years, 24 (39.3%) and functionary positions (commissions, committees, work teams) 40 (65, 6%). 52 (85.2%) good category downward communication, 53 (86.9%) good category upward communication, 54 (88.5%) good horizontal communication and 58 good category performance (95. 1%). Downward communication obtained a p_value of 0.01, upward communication of a p_value of 0.00 and horizontal communication with a p_value of 0.00 for all variables ≤ 0.005. The conclusion is that communication has a positive effect on the performance of the functional service of the Javanese Klampok Christian Church, Banjarnegara Regency.